Highly selective and efficient synthesis of 3-arylamino-substituted 5-aminopyrazole-4-carboxylates under microwave irradiation - Lim, F.; Gan, R.; Dolzhenko, Anton (Pergamon, 2016)
© 2017 Elsevier Ltd.An improved microwave-assisted method was developed for the preparation of ethyl 5-aminopyrazole carboxylates from ethyl 2-cyano-3-methylthioacrylates and hydrazine. It was shown that using microwave irradiation significantly reduced the reaction time and improved the process selectivity and yield. The reaction proved to be reproducible in different microwave reactors and on large scale, affording the desired products in high yields and purity. A representative library of 3-arylamino-substituted 5-aminopyrazole-4-carboxylates was successfully prepared to assess the scope of the method.